EFFECT OF AGING TIME TOWARD CRYSTALLINITY OF PRODUCTS IN SYNTHESIS OF MESOPOROUS SILICATES MCM-41 - Suyanta Suyanta; Narsito Narsito; Endang Tri Wahyuni; Triyono Triyono; Sutarno Sutarno (Universitas Gadjah Mada, 2010)
Researches about the effects of aging time toward crystallinity of products in the synthesis of mesoporous silicates MCM-41 have been done. MCM-41 was synthesized by hydrothermal treatment to the mixture of sodium silicate, sodium hydroxide, cetyltrimetylammoniumbromide (CTMAB) and aquadest in the molar ratio of 8Na2SiO3 : CTMAB : NaOH : 400H2O. Hydrothermal treatment was carried out at 110 °C in a teflon-lined stainless steel autoclave heated in the oven, with variation of aging time, i.e.: 4, 8, 12, 16, 24, 36, 48, and 72 h respectively. The solid phase were filtered, then washed with deionised water, and dried in the oven at 100 °C for 2 h. The surfactant CTMAB was removed by calcinations at 550 °C for 10 h with heating rate 2 °C/min. The as-synthesized and calcined powders were characterized by using FTIR spectroscopy and X-ray diffraction method. The relative crystallinity of products was evaluated based on the intensity of d100 peaks. The best product was characterized by using N2 physisorption method in order to determine the specific surface area, mean pore diameter, lattice parameter, and pore walls thickness. It was concluded that the relative crystallinity of the products was sensitively influenced by the aging time. The highest relative crystallinity was achieved when used 36 h of aging time in hydrothermal treatment. In this optimum condition the product has 946.607 m2g-1 of specific surface area, 3.357 nm of mean pore diameter, 4.533 nm of lattice parameter, and 1.176 nm of pore walls thickness.